2010
DOI: 10.1176/appi.ajp.2009.09040576
|View full text |Cite
|
Sign up to set email alerts
|

Association of FKBP5 Polymorphisms With Suicidal Events in the Treatment of Resistant Depression in Adolescents (TORDIA) Study

Abstract: Objective-The authors sought to assess the relationship between candidate genes and two clinical outcomes, namely, symptomatic improvement and the occurrence of suicidal events, in a sample of treatment-resistant depressed adolescents. Method-A subsample of depressed adolescents participating in the Treatment of SSRI-ResistantDepression in Adolescents (TORDIA) trial, 155 of whom were of European origin, were genotyped with respect to 21 polymorphisms on 12 genes that have a reported association with depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
1
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(124 citation statements)
references
References 40 publications
6
114
1
3
Order By: Relevance
“…However, we found one SNP within GDA, which was associated in the GENDEP GWAS approach, significantly associated with TESI. Moreover, we found further evidence for FKBP5 and ABCB1 to be implicated in TESI, which were previously reported in two other candidate gene approaches on emerging or worsening of suicidal ideation (Brent et al, 2010a;Perroud, 2011).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, we found one SNP within GDA, which was associated in the GENDEP GWAS approach, significantly associated with TESI. Moreover, we found further evidence for FKBP5 and ABCB1 to be implicated in TESI, which were previously reported in two other candidate gene approaches on emerging or worsening of suicidal ideation (Brent et al, 2010a;Perroud, 2011).…”
Section: Discussionsupporting
confidence: 86%
“…In candidate gene studies, associations with suicidal ideation were found with genetic markers within the genes encoding the glutamate receptors GRIK2 and GRIA3 (Laje et al, 2007), and the cyclic adenosine response-element binding protein (CREB1) (Perlis et al, 2007b) in the STAR*D cohort and the genes encoding brain-derived neurotrophic factor (BDNF), the neurotrophic tyrosine kinase receptor type 2 (NTRK2), and a-2 adrenergic receptor (ADRA2A) (Perroud et al, 2009) in GENDEP. Further candidate gene approaches revealed associations of markers within FK506-binding protein 5 (FKBP5) in the Treatment of Resistant Depression in Adolescents (TORDIA) study (Brent et al, 2010a) and in FKBP5 and ATP-binding cassette, subfamily B (MDR/TAP), member 1 (ABCB1) in a sample of depressed outpatients . Previously, markers of the two glutamatergic receptor genes could be partly replicated in our Munich Antidepressant Response Signature (MARS) project (http://www.mars-depression.de), an independent sample consisting mainly of individuals of German origin (Menke et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, T homozygotes were found to exhibit elevated cortisol levels during recovery after stress (Ising et al 2008). In line with this, rs1360780 has been associated with psychopathology such as mood disorders (Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and suicidality (Brent et al 2010). Moreover, this SNP has been shown to interact with childhood abuse in predicting PTSD symptoms (Binder et al 2008) and susceptibility to depression (Appel et al 2011), with an increased risk in the TT genotype following childhood abuse.…”
Section: Introductionmentioning
confidence: 77%
“…In humans, healthy adults homozygous for these alleles show a greater and more prolonged cortisol response during the Trier Social Stress Test compared with those who have complementary genotypes (Ising et al, 2008). These SNPs, as well as rs9296158 and rs9470080, have been associated with a higher FKBP5 expression and a stronger induction of FKBP5 mRNA by cortisol (Binder et al, 2004;Tatro et al, 2010), and subsequently have been correlated with depression (Binder et al, 2004;Tatro et al, 2010) and suicide (Brent et al, 2010;Perez-Ortiz et al, 2013). They also affect cortisol responses and result in diminished dexamethasone suppression (Binder et al, 2008).…”
Section: Discussionmentioning
confidence: 99%